Visualizing Neuropharmacological Effects of Guanfacine Extended Release in Attention Deficit Hyperactivity Disorder Using Functional Near-Infrared Spectroscopy - Ikeda, Takahiro; Inoue, Akari; Tanaka, Daisuke; Hashimoto, Tamao; Sutoko, Stephanie; Tokuda, Tatsuya; Kyutoku, Yasushi; Maki, Atsushi; Yamagata, Takanori; Dan, Ippeita; Monden, Yukifumi (Frontiers in Neuroergonomics, 2021)
Objective: In the current study, we explored the neural substrate for acute effects of guanfacine extended release (GXR) on inhibitory control in school-aged children with attention deficit hyperactivity disorder (ADHD), using functional near-infrared spectroscopy (fNIRS). Methods: Following a GXR washout period, 12 AD HD children (6–10 years old) performed a go/no-go task before and 3 h after GXR or placebo administration, in a randomized, double-blind, placebo-controlled, crossover design study. In the primary analysis, fNIRS was used to monitor the right prefrontal cortical hemodynamics of the participants, where our former studies showed consistent dysfunction and osmotic release oral system-methylphenidate (OROS-MPH) and atomoxetine hydrochloride (ATX) elicited recovery. We examined the inter-medication contrast, comparing the effect of GXR against the placebo. In the exploratory analysis, we explored neural responses in regions other than the right prefrontal cortex (PFC). Results: In the primary analysis, we observed no significant main effects or interactions of medication type and age in month (two-way mixed ANCOVA, Fs < 0.20, all ps > .05). However, in the post-hoc analysis, we observed significant change in the oxy-Hb signal in the right angular gyrus (AG) for inter-medication (one sample t-test, p < 0.05, uncorrected, Cohen's d = 0.71). Conclusions: These results are different from the neuropharmacological effects of OROS-MPH and ATX, which, in an upregulated manner, reduced right PFC function in ADHD children during inhibitory tasks. This analysis, while limited by its secondary nature, suggested that the improved cognitive performance was associated with activation in the right AG, which might serve as a biological marker to monitor the effect of GXR in the ADHD children.